Efficacy of a gB + gD-based subunit vaccine and the adjuvant granulocyte-macrophage colony stimulating factor for pseudorabies virus in rabbits - Cao, Zhi; Zhang, Ke; Zhang, Heng; Zhang, Hongliang; Yu, Ying; Yin, Dehua; Shan, Hu; Qin, Zhihua (Frontiers in Microbiology, 2022)
Pseudorabies (PR), which is caused by the pseudorabies virus (PRV), is a severe infectious disease that causes abortions in adult sows and fatal encephalitis in piglets; the disease can occur in pigs of all ages and other mammals, which can lead to significant economic loss around the worldwide. The new PRV variant invalidated the available commercial attenuated and inactivated vaccines. Consequently, subunit vaccines have been suggested as novel strategies for PR control, while they are usually formulated with adjuvants due to their lower immunogenicity. We aimed to select a safe and efficient adjuvant for subunit vaccines for PR. In our study, glycoprotein B (gB) and glycoprotein D (gD) were expressed based on a baculovirus expression system, and granulocyte-macrophage colony stimulating factor (GM-CSF) was expressed using an Escherichia coli (E. coli) expression system; subsequently, a gB+gD subunit vaccine adjuvanted by GM-CSF was constructed. A rabbit model infected with a PRV SD-2017 strain was established, the TCID50 and LD50 were measured, and the typical clinical symptoms were observed. After a lethal challenge of 5 LD50 with a PRV SD-2017 strain, the rabbits exhibited typical clinical symptoms, including itching and high temperature, and histopathology revealed severe inflammation in the brain, which is the dominant target organ of PRV. Rabbits immunized with the gB+gD+GM-CSF subunit vaccines produced higher levels of antibodies than those immunized with gB+gD+ISA 201, which was adjuvanted with a frequently used oil adjuvant. The survival rate of rabbits vaccinated with gB+gD+GM-CSF was 100%, which was superior to that of rabbits vaccinated with gB+gD+ISA 201 (80%), inactivated PRV+GM-CSF (60%) and commercial inactivated vaccine (60%) after challenge with PRV SD-2017. These data suggested that the gB+gD+GM-CSF-based subunit vaccine had good protective efficacy against the PRV SD-2017 strain in rabbits and that GM-CSF could be developed as a candidate adjuvant for use in a vaccine regimen to prevent and even eradicate PR.